2003
DOI: 10.1002/chin.200334177
|View full text |Cite
|
Sign up to set email alerts
|

Steroidal Saponins from Rhizomes of Tupistra wattii Hook. f.

Abstract: Steroids Steroids U 0300Steroidal Saponins from Rhizomes of Tupistra wattii Hook. f. -[isolation, structure elucidation and cytotoxicity of three new spirostanol saponins such as (I)] -(SHEN, P.; WANG, S.-L.; LIU, X.-K.; YANG, C.-R.; CAI, B.; YAO*, X.-S.; Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…(), this is the first report of antifungal activity by this compound. Other spirostanol saponins isolated from the Solanaceae as well as from other plant families have also been reported to have antifungal activities (Alvarez et al ., ; Haraguchi et al ., ; Shen et al ., ; González et al ., ; Yang et al ., ; Lu et al ., ). Our observation that compound 1 inhibits growth of the human pathogens C. albicans and C. neoformans suggests it has potential applications in treating mycoses such as ringworm, athletes foot, and onychomycoses fungal infections of the nails.…”
Section: Discussionmentioning
confidence: 99%
“…(), this is the first report of antifungal activity by this compound. Other spirostanol saponins isolated from the Solanaceae as well as from other plant families have also been reported to have antifungal activities (Alvarez et al ., ; Haraguchi et al ., ; Shen et al ., ; González et al ., ; Yang et al ., ; Lu et al ., ). Our observation that compound 1 inhibits growth of the human pathogens C. albicans and C. neoformans suggests it has potential applications in treating mycoses such as ringworm, athletes foot, and onychomycoses fungal infections of the nails.…”
Section: Discussionmentioning
confidence: 99%
“…T. chinensis, T. wattii, and T. yunnanensis are main sources of spirostanol and furostanol saponins. Sixty-five compounds were assigned as spirostanol saponins (Table 1 and Figure 2), 2,[7][8][9][10]21,22,24,28,[31][32][33]35,36,39 while compounds 85 to 150 are furostanol saponins (Table 1 and Figure 3). 5,8,10,18,22,24,31,35,37,[39][40][41][42][43][44][45][46][47] Taking spirostanol saponins into consideration, glycosylation generally happens at C-1, C-3, C-5, and C-24.…”
Section: Spirostanol and Furostanol Saponinsmentioning
confidence: 99%
“…In the genus Tupistra, convallagenin A 3-O-β-D-glucopyranoside (30) and convallagenin B 5-O-β-D-glucopyranoside (31) have only been isolated from the rhizomes of T. chinensis and T. wattii, respectively. 9,32 The underground part of T. chinensis seems to be a good reservoir of spirostanol saponins. Based on physicochemical results and NMR spectral analysis, Song et al reported that the 65% EtOH extract of T. chinensis underground parts contained 2 new spirostanol saponins, (24S,25R)-1β-hydroxy-3β-[(β-Dglucopyranoside)oxy]-spirost-5-en-24-yl-β-D-glucopyranoside (34), and (24S)-spirost-25 (27)-en-1β,3β,4β,5β,6β,24β-hexahydroxy-24-O-β-D-glucopyranoside (59), in addition to 2 known ones, 3-epi-diosgenin-3-β-D-glucopyranoside (32), and 25(R)-1β-hydroxy-spirost-5-en-3α-yl-O-β-D-glucopyranoside [3-epi-ruscogenin-3-β-D-glucopyranoside] (35).…”
Section: Spirostanol and Furostanol Saponinsmentioning
confidence: 99%
See 2 more Smart Citations